2007
DOI: 10.1253/circj.72.575
|View full text |Cite
|
Sign up to set email alerts
|

Peak VO2 is More Potent Than B-Type Natriuretic Peptide as a Prognostic Parameter in Cardiac Patients

Abstract: These results indicate that peak VO(2) is more potent than BNP for predicting the mortality in patients with mixed cardiac disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 31 publications
(16 reference statements)
1
20
0
Order By: Relevance
“…[17][18][19][20] In this study, we demonstrated that an increase in IMA after EST suggests a large ischemic burden of CAD.…”
Section: Discussionsupporting
confidence: 50%
“…[17][18][19][20] In this study, we demonstrated that an increase in IMA after EST suggests a large ischemic burden of CAD.…”
Section: Discussionsupporting
confidence: 50%
“…Twenty-three studies were based in Europe, 8 -28,46,47 5 in North America, 29 -33 1 in Australia and New Zealand, 34 and 7 in East Asia [35][36][37][38][39][40]45 (predominantly in Japan), and 4 were multinational. [41][42][43][44] Thirty-six studies were prospective cohorts and 4 "nested" case-control studies; 14 studies recruited participants from population registers (such as general practitioners' lists or electoral rolls), and 26 were hospital based (of which 10 were clinical trials).…”
Section: Resultsmentioning
confidence: 99%
“…14,15 It has been well documented that recovery V • O2 is prolonged in patients with heart failure. 12, 16 Pavia et al reported that T1/2 V…”
Section: Discussionmentioning
confidence: 99%